Stardust and feminism: A creatureliness agenda - Nancy K. Dess (Frontiers in Psychology)
People are living, breathing creatures. Dominant feminist discourses are situated within hegemonic human exceptionalism (HHE) which, by framing the body in terms of human forms of meaning-making and social life, eschews first-order embodiment (or creatureliness) as worthy of inquiry. Here, well-known reasons for avoidance of “the biological” are briefly summarized and an argument is advanced for meta-theoretical centering of creatureliness. A three-pronged agenda is proposed that embraces the creaturely body without the “-isms” (e.g., essentialism) and “-izings” (e.g., so-called “naturalizing”) that subvert feminist commitments. By unsettling HHE, executing the agenda would promote broader feminist coalitions and new scholarly collaborations aimed at fleshing out gender.